Equilíbrio postural e independência funcional de idosos de acordo com o sexo e a idade: Estudo transversal - Nakagawa, Helen Benincasa [UNESP]; Ferraresi, Juliana Rizzatto; Prata, Melina Galetti; Scheicher, Marcos Eduardo [UNESP] (FapUNIFESP (SciELO), 2017)
CONTEXT AND OBJECTIVE: Aging causes changes in men and women. Studies have shown that women have worse postural balance and greater functional dependence than men, but there is no consensus regarding this. The aim of this study was to compare the balance and functional independence of elderly people according to sex and age, and to evaluate the association between postural balance and the number of drugs taken. DESIGN AND SETTING: Cross-sectional at a state university. METHODS: 202 elderly people were evaluated regarding balance (Berg Scale), independence (Barthel Index), age, sex, number of medications and physical activity. RESULTS: The subjects comprised 117 women (70.2 ± 5.6 years old) and 85 men (71.1 ± 6.9 years old). For balance, there was no significant difference regarding sex, but there was a difference regarding age (P < 0.0001). For functional independence, there was a difference regarding sex (P = 0.003), but not regarding age. The variables of age, medications and physical activity were significant for predicting the Berg score. For the Barthel index, only age and sex were significant. Elderly people who took three or more medica-tions/day showed higher risk of falling than those who took up two drugs/day (odds ratio = 5.53, P < 0.0001, 95% confidence interval, 2.3-13.0). CONCLUSIONS: There was no sexual difference in relation to postural balance. However, people who were more elderly presented a high risk of falling. Functional dependence was worse among females. There was an association between the number of medication drugs and risk of falling.
Postural balance and functional independence of elderly people according to gender and age: Cross-sectional study
Keywords: Accidental falls; Activities of daily living; Aging; Drug therapy; Postural balance